An Ultra‐Broadband High Efficiency Polarization Beam Splitter for High Spectral Resolution Polarimetric Imaging in the Near Infrared (Adv. Sci. 27/2022). Issue 27 (23rd September 2022) - Hsiao, Hui‐Hsin; Muller, Richard E.; McGuire, James P.; Nemchick, Deacon J.; Shen, Chin‐Hung; Harten, Gerard van; Rud, Mayer; Johnson, William R.; Nordman, Austin D.; Wu, Yen‐Hung; Wilson, Daniel W.; Chiou, Yih‐Peng; et al.
Abstract : Ultra‐Broadband, High Efficiency Polarized Beam Splitter Metagrating In article number 2201227, Hui‐Hsin Hsiao, Richard E. Muller, Dejian Fu, and co‐workers demonstrate a polarized beam splitter metagrating that enables simultaneous measurement of four spatialspectral‐ polarimetric images with an efficiency of 70% and a polarimetric contrast greater than 0.996 in the entire near‐infrared oxygen bands, which will be integrated into NASA's high‐resolution multiplespecies atmospheric profiler instrument for vertical profiling of global aerosols.